FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA BANK UMUM SYARIAH DI INDONESIA - Suryani, Yani; Ika, Desi (Universitas Medan Area, 2019)
This study aims to know the effect of the determinant variables on profit growth in Islamic commercial banks in Indonesia. During the period of financial crisis in 1997 Islamic banks were still able to show relatively better performance compared to conventional banking institutions. Due to the lower distribution of non-performing loans (non-performing loans) to the Islamic banks and no negative spreads in their operational activities, this condition as well as profit growth generated by Islamic banks. This study analyzes the effect of Net Operational Income (NOI), Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and operational costs to operational income (BOPO) both partially or simultaneously on the Profit Growth of Islamic commercial banks in Indonesia in the 2016-2018 period. The type of research is associative, secondary data sources and data are analyzed quantitatively. The results of this study indicate that partially Net Operating Income (NOI) affects the profit growth of Islamic Commercial Banks in Indonesia. For simultaneous testing the overall determinant variable does not affect earnings growth at Islamic Commercial Banks in Indonesia.